Analisis Pengaruh Kondisi Perkerasan Jalan Terhadap Kecepatan Kendaraan - M Novrizal Elsandi; Leo Santosa; Gunawan Wibisono (LPPM Universitas Abdurrab, 2025)
Roads are transportation infrastructures that play an important role in supporting community mobility and regional development. The Dompas-Sepotong (Siak Regency Border) road segment has suffered various damages, causing inconvenience and losses to its users. These damages impact user comfort and result in longer travel times. This study aims to determine the condition of the road pavement and the relationship between road condition and vehicle speed. The method used to assess the pavement condition is the Pavement Condition Index (PCI) method, as it is widely adopted and internationally accepted. Meanwhile, vehicle speed was measured through a moving vehicle survey based on Bina Marga Guideline No. 001/T/BNKT/1990. The correlation between road condition and vehicle speed was analyzed using regression analysis. The results of the study indicate various types of damage such as joint cracking, edge cracking, shoulder subsidence, alligator cracking, raveling, potholes, and aggregate polishing, with an average PCI value of 80, which falls into the